Financial penalties and bank performance - Köster, Hannes; Pelster, Matthias (Journal of Banking & Finance, 2017)
This paper investigates the impact of financial penalties on the profitability and stock performance of banks. Using a unique dataset of 671 financial penalties imposed on 68 international listed banks over the period 2007 to 2014, we find a negative relation between financial penalties and pre-tax profitability but no relation with after-tax profitability. This result is explained by tax savings, as banks are allowed to deduct specific financial penalties from their taxable income. Moreover, our empirical analysis of the stock performance shows a positive relation between financial penalties and buy-and-hold returns, indicating that investors are pleased that cases are closed, that the banks successfully manage the consequences of misconduct, and that the financial penalties imposed are smaller than the accrued economic gains from the banks’ misconduct. This argument is supported by the positive abnormal returns accompanying on the announcement of a financial penalty.